A imaginação melodramática e o cinema de Pedro Almodovar - Oliveira, Caroline Anielle Souza Batista Pires de (2013)
This paper proposes the questioning and appropriation of the concept of imagination melodramatic , coined by Peter Brooks (1995 ) , in cinema. We apply the method of film analysis in the film Women on the Verge of a Nervous Breakdown (1988 ) by filmmaker Pedro Almodovar . We chose to dedicate ourselves to the analysis of a film that departs in some respects from the classical structure of cinema, just to understand, with more depth , strength and inexhaustible vitality of the melodramatic imagination . In this process , it is necessary to recover the historical birth of melodrama and its recurrence in the theater so we can understand more clearly the breadth and scope of the concept . Question the concept of melodrama as a genre and work with the hypothesis of a melodramatic imagination before being impregnated in various theatrical and film productions , is built mainly by the look that the public launches on the work . The melodrama , or rather this imagination , thus , would be a lens through which the modern individual would structure and accelerated relatively solidly values appease him, at least superficially .